Learning Interactive For Increase Ability Reading for Children - Rihana; Nurbiana Dhieni; Nurjannah (Jipmor: Jurnal Ilmu Pendidikan Dan Humaniora, 2023)
Early childhood educators are stimulating aspects of children's cognitive development. Cognitive development is a human thought process to assess, connect, and consider a particular problem. Cognitive development in children refers to the way of thinking, reasoning, solving problems, and being able to use various symbols such as words, images, gestures, and numbers. The objectives of this study are: 1) obtain information 2) produce interactive learning multimedia that is appropriate for initial reading skills; 3) to determine the effectiveness of the media produced for the child's early reading ability. This research is a type of research and development that refers to the Dick & Carey model. The research stage conducted was 9 out of 10 stages of the Dick & Carey model. The population in the study consisted of 3 schools totaling 60 students. The sampling technique is purposive sampling with a sample of 27 people consisting of one-to-one evaluation subjects of 3 children in one school. The subject of small group evaluation is 9 people in one different school. The subject of the field trial evaluation is one class, namely 15 people in one different school. The data collection instruments used are questionnaires, observations, and tests. Data analysis was carried out in a qualitative descriptive and quantitative descriptive manner. The results of the study are as follows. (1) Multimedia Development of Interactive Learning There are several media in it, namely text, audio, visual, color , and animation. (2) Multimedia interactive learning is packaged into a flash disk with elements such as text, visuals, colors , audio, and animation. (3) Multimedia interactive learning can improve children's early reading abilities. The average score of the pretest was 70.7 and the average posttest was 95. It can be seen that the average score of children increased by 26% after using interactive learning multimedia. It was concluded that multimedia interactive learning can improve early childhood reading skills